Pengembangan Handout Bahasa Indonesia Bermuatan Kearifan Lokal Pada Siswa Kelas V di MI DDI Tani Aman Samarinda - Ramadanti, Nur Fitri; Idris, Husni; Khotimah, Khusnul (Faculty of Education and Teacher Training of UINSI Samarinda, 2025)
This study is a research and development (R&D) study that adapts the ADDIE model with adjustments based on the needs of the researcher. The purpose of this study is to produce an Indonesian handout product containing local wisdom and the level of validity of the Indonesian handout containing local wisdom for fifth grade students at MI DDI Tani Aman Samarinda. The implementation of this study includes validation tests by material experts and media experts, readability tests by small groups and large groups, and teacher responses related to the products developed. The results of the study showed that the developed product was said to be feasible by material experts and media experts with a percentage of material expert assessment of 73.68% and a media expert assessment of 90.93%. The results of the readability test in the small group were 90% and the large group was 89.16%. The results of the responses of teachers who teach the Indonesian Language study field for fifth grade were 81.54%. This indicates that the Indonesian handout containing local wisdom produced in this study is declared feasible to be implemented in the learning process in Indonesian at MI DDI Tani Aman Samarinda.